1985
DOI: 10.1161/01.cir.72.6.1293
|View full text |Cite
|
Sign up to set email alerts
|

Further observations on transient entrainment: importance of pacing site and properties of the components of the reentry circuit.

Abstract: Transient entrainment of circus-movement tachycardia utilizing an atrioventricular (AV) bypass pathway was studied in 13 patients (nine with the orthodromic form, two with the antidromic form, and two with both the orthodromic and antidromic forms). All patients had a leftsided AV bypass pathway. Pacing at selected rates faster than the spontaneous rate was performed during the tachycardia at a site proximal or distal to the AV node, an area of slow conduction within the reentry loop. Rapid pacing from a site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(40 citation statements)
references
References 18 publications
1
39
0
Order By: Relevance
“…Furthermore, the EAAS was orthodromically captured during manifest entrainment. Orthodromic capture of the EAAS during manifest entrainment implies that there is an area of slow conduction within the reentry circuit between the entrance and exit sites 11, 12. Satoh et al15 clearly demonstrated that orthodromic capture of the EAAS implies the presence of an entrance and an exit to the atrium located at distinct different locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the EAAS was orthodromically captured during manifest entrainment. Orthodromic capture of the EAAS during manifest entrainment implies that there is an area of slow conduction within the reentry circuit between the entrance and exit sites 11, 12. Satoh et al15 clearly demonstrated that orthodromic capture of the EAAS implies the presence of an entrance and an exit to the atrium located at distinct different locations.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the EnSite 3000 system have been previously described 10. The proximity of the SCZ in the reentry circuit was identified utilizing an entrainment technique 11. While recording the contact atrial electrogram at the EAAS, rapid atrial pacing at a rate 5 beats per minute faster than the tachycardia rate was delivered to demonstrate manifest entrainment and orthodromic capture of the EAAS12 (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…AFL was defined as a macroreentrant atrial tachycardia displaying (1) typical "sawtooth" flutter wave appearance on the surface ECG with a constant morphology, (2) entrainment criteria, 11,12 with demonstration of an excitable gap, and (3) a regular and constant epicardial atrial activation pattern (ie, no change in sequence) recorded from the 3 epicardial electrode plaques.…”
Section: Afl Inductionmentioning
confidence: 99%
“…When the first postpacing interval was the same as the paced cycle length, the atrial electrogram at the recording site of the His bundle potential was considered to be captured orthodromically. [14][15][16][17] Results…”
Section: Induction Ofavnrtmentioning
confidence: 99%